Critical Appraisal of e-learning through Mobile Devices in Medical Education - Gaurav Sawarkar1 , Punam Sawarkar2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Summary: In COVID-19 pandemic, e-learning is the essential component of education system. All theschools, colleges, universities implemented e-learning program for the purposes of teaching and learning.Syllabus of new session is started for the said academic year through e-learning to minimize the academic lossand to coverup the academic session. Nowadays, medical education is full off with information technologysolutions, computer--assisted learning has facilitated teaching of a wide range of topics, including basicscience and advanced surgical procedures. The e-learning is totally depending upon the expertise in thehandling of technology, electronic devices as well resource material available for the conduction of e-classesand one of the most important factors i.e. internet connectivity. In due course, mental status of students andteachers along with motivation from the teaching institute is also important factor for e-learning program.There were various challenges and disadvantages reported in previous research studies regarding e-learning,suggested for periodic need assessment of educational program, emphasize upon breach in between expectedand existing system, resources management system, technical expert team, financial budget, mindset of theteachers and students and training sessions for development of e-learning culture.